Value of accelerated hyperfraction dozes of radiation in primary radiation treatment for Hodgkin’s lymphoma - N. V. Ilyin; J. N. Vinogradova; E. N. Nikolaeva; E. V. Smirnova (Онкогематология)
Methods: Were examined 145 patients with Hodgkin’s lymphoma (HL) II-IIIAB who received AHF within 1985-1997. A comparison was carried out with the comparable group of 110 patients given CF. The AHF schedule was carried out by admission of the single dose 1,35 Gy twice a day with interval 3,54 hs to basic registration points (bifurcation of trachea and paraaortal lymphatic nodes). The total doses in clinically involved nodes were approximately 40 Gy; zones of subclinical involvement — 36 Gy.Results: Objective response was obtained 87,4% in the AHF group and 90,0% in the CF group. Median follow-up was 144 months: AHF - 144 months, CF — 150 months. Quantity of recurrences was significantly higher in patients with CF than in those with AHF — 28,3% and 16,5% (p=0,02), respectively. 10-years overall survival was 82,8% in AHF group and 72,1% in the CF group. 10-year recurrence-free survival was 81,5% in the AHF group and 69,8% in the CF group (p=0,04). Analysis of clinical date showed essential reduction of radiation pneumonitis rate at AHF in comparison with CF: 13,1% vs. 25,4% (p=0,01), postradiation pericarditis: 2,1% vs. 7,3% (p=0,04), leucopenia grade IV: 4,1% vs. 12,7%.Conclusions: Clinical analysis revealed the benefits of single dose decrease from 2 Gy to 1,35 Gy at the twice a day irradiation scheme. The AHF is an effective schedule of RT and promotes to the recurrence frequency reduction, increases recurrence-free survival, decreases of the cardiopulmonary complication risk and leucopenia rate.